Method for producing positive electrode composition and method for producing positive electrode

The method for manufacturing a positive electrode composition by mixing binders, carbon black, carbon nanotubes, and active materials addresses the challenges of discharge rate and cycle characteristics in lithium-ion secondary batteries, resulting in improved battery performance and longevity.

JP7649866B2Active Publication Date: 2025-03-21DENKA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023543826
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-27
Filing Date
2022-08-16
Publication Date
2025-03-21
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries face challenges in achieving excellent discharge rate characteristics and cycle characteristics, which are crucial for high-energy density and long-term reliability.

Method used

A method for manufacturing a positive electrode composition that involves mixing a binder with a first liquid medium, carbon black with a second liquid medium, and carbon nanotubes with a third liquid medium, followed by the addition of an active material to obtain a uniform and conductive positive electrode composition.

Benefits of technology

The method results in a lithium-ion secondary battery with enhanced discharge rate characteristics and cycle characteristics, ensuring improved performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649866000001
    Figure 0007649866000001
Patent Text Reader

Abstract

Provided is a method for producing a positive electrode composition, the method comprising: a first step for obtaining a mixture by mixing a first agent containing a binder and a first liquid medium, a second agent containing carbon black and a second liquid medium, and a third agent containing carbon nanotubes and a third liquid medium; and a second step for obtaining a positive electrode composition by mixing the mixture and an active substance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode composition and a method for producing a positive electrode. [Background technology]

[0002] In light of growing environmental and energy issues, there has been active development of technologies aimed at realizing a low-carbon society that reduces dependency on fossil fuels. Such technological development is wide-ranging, and includes the development of low-emission vehicles such as hybrid electric vehicles and electric vehicles, natural energy power generation and storage systems such as solar and wind power generation, and next-generation power transmission networks that supply electricity efficiently and reduce transmission losses.

[0003] Batteries are one of the key devices commonly required for these technologies, and high energy density is required for such batteries to miniaturize the systems. In addition, high output characteristics are required to enable stable power supply regardless of the temperature of the operating environment. Furthermore, good cycle characteristics that can withstand long-term use are also required. For this reason, conventional lead-acid batteries, nickel-cadmium batteries, and nickel-metal hydride batteries are being rapidly replaced by lithium-ion secondary batteries, which have higher energy density, output characteristics, and cycle characteristics.

[0004] Conventionally, the positive electrode of a lithium-ion secondary battery is manufactured by coating a positive electrode paste containing a positive electrode active material, a conductive material, and a binding material (also called a binder) on a current collector. Lithium-containing composite oxides such as lithium cobalt oxide and lithium manganese oxide have been used as the positive electrode active material. In addition, since the positive electrode active material has poor conductivity, a conductive material such as carbon black has been added to the positive electrode paste in order to impart conductivity (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-227481 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for further improvement in the performance of lithium ion secondary batteries.

[0007] The present invention aims to provide a positive electrode composition capable of obtaining a lithium ion secondary battery having excellent discharge rate characteristics and cycle characteristics, and a method for producing a positive electrode capable of realizing a lithium ion secondary battery having excellent discharge rate characteristics and cycle characteristics. [Means for solving the problem]

[0008] The present invention relates to, for example, the following <1> ~ <6> Regarding. <1> A method for producing a positive electrode composition, comprising: a first step of mixing a first agent containing a binder and a first liquid medium, a second agent containing carbon black and a second liquid medium, and a third agent containing carbon nanotubes and a third liquid medium to obtain a mixed liquid; and a second step of mixing the mixed liquid with an active material to obtain a positive electrode composition. <2> A method for producing a positive electrode composition, comprising: a first step of mixing a first agent containing a binder and a first liquid medium with a second agent containing carbon black and a second liquid medium to obtain a first mixed liquid; a second step of mixing the first mixed liquid with a third agent containing carbon nanotubes and a third liquid medium to obtain a second mixed liquid; and a third step of mixing the second mixed liquid with an active material to obtain a positive electrode composition. <3> The carbon black is 100 to 400 m 2 / g BET specific surface area and a crystallite size (Lc) of 15 to 26 Å. <1> or <2> The manufacturing method described in <4> The carbon nanotubes have an average diameter of 5 to 15 nm, and the ratio of the average diameter to the BET specific surface area of ​​the carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m2 / g), <1> ~ <3> 13. The method for producing a semiconductor device according to claim 12, <5> The content of the carbon black is 40 to 90 mass% based on the total amount of the carbon black and the carbon nanotubes. <1> ~ <4> 13. The method for producing a semiconductor device according to claim 12, <6> <1> ~ <5> and a second step of applying the positive electrode composition onto a current collector to form a composite layer containing the carbon black, the carbon nanotubes, the binder, and the active material on the current collector. Effect of the Invention

[0009] According to the present invention, there is provided a positive electrode composition capable of obtaining a lithium ion secondary battery having excellent discharge rate characteristics and cycle characteristics. Also, according to the present invention, there is provided a method for producing a positive electrode capable of realizing a lithium ion secondary battery having excellent discharge rate characteristics and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Preferred embodiments of the present invention will now be described in detail.

[0011] The method for producing a positive electrode composition of the present embodiment is a method for obtaining a positive electrode composition by mixing, in a predetermined order, a first agent containing a binder and a first liquid medium, a second agent containing carbon black and a second liquid medium, a third agent containing carbon nanotubes and a third liquid medium, and an active material.

[0012] According to the method for producing a positive electrode composition of the present embodiment, a positive electrode composition that can achieve excellent discharge rate characteristics and cycle characteristics can be obtained, compared to a case in which carbon black, carbon nanotubes, a binder, and an active material are mixed simultaneously.

[0013] In this embodiment, carbon black and carbon nanotubes function as conductive materials. The basic role of the conductive material is to impart conductivity to the poorly conductive positive electrode active material. In addition, in a lithium ion secondary battery, the positive electrode active material expands and contracts as the charge and discharge are repeated, so that the contact points between the positive electrode active materials are gradually lost, but the conductive material also plays a role in connecting the positive electrode active materials that have lost their contact points. If the dispersibility of the conductive material in the positive electrode active material is poor, the positive electrode active material and the conductive material cannot be in sufficient contact with each other, making it difficult to form a conductive path, and a problem occurs in that the performance of the active material cannot be fully brought out. As a result, since a portion with poor conductivity appears locally in the positive electrode, the active material is not fully utilized, the discharge capacity is reduced, and the battery life is shortened. In addition, it is considered that the content of the conductive material is increased to ensure the conductive path, but from the viewpoint of improving the battery characteristics, it is desirable to reduce the content of the conductive material that does not contribute to the charge and discharge capacity in the positive electrode and increase the content of the positive electrode active material. According to the method for producing the positive electrode composition of the present embodiment, aggregation of the carbon black and the carbon nanotubes is suppressed and uniform dispersion of the conductive material is ensured, so that it is believed that excellent battery characteristics can be obtained even when the active material content is high.

[0014] The method for producing the positive electrode composition of the present embodiment may be, for example, the following first aspect or the following second aspect.

[0015] In a first aspect, a method for producing a positive electrode composition includes a first step of mixing a first agent containing a binder and a first liquid medium, a second agent containing carbon black and a second liquid medium, and a third agent containing carbon nanotubes and a third liquid medium to obtain a mixed liquid, and a second step of mixing the mixed liquid with an active material to obtain a positive electrode composition.

[0016] According to the first aspect, a positive electrode composition capable of realizing excellent discharge rate characteristics and cycle characteristics can be obtained, compared to a case where carbon black, carbon nanotubes, a binder, and an active material are simultaneously mixed. The reason why the manufacturing method of the first aspect exhibits the above-mentioned effects is considered to be that in the first step, an interaction between the binder and the carbon black realizes a dispersed state in which the carbon black is less likely to aggregate and is less likely to be entangled with the carbon nanotubes, thereby suppressing the non-uniformity of the electrode structure caused by the aggregation of the carbon black or the entanglement of the carbon black and the carbon nanotubes.

[0017] The first step of the first aspect is a step of mixing a first agent containing a binder and a first liquid medium, a second agent containing carbon black and a second liquid medium, and a third agent containing carbon nanotubes and a third liquid medium to obtain a mixed liquid.

[0018] In the first step of the first embodiment, the method of mixing the first agent, the second agent, and the third agent is not particularly limited, and may be carried out by a known method (e.g., stirring and mixing using a ball mill, a sand mill, a twin-screw kneader, a centrifugal mixer, a planetary mixer, a dispersing mixer, etc.). The first step of the first embodiment may be, for example, a step of charging the first agent, the second agent, and the third agent into a mixing vessel, and then stirring to obtain a mixed liquid.

[0019] The second step in the first embodiment is a step of mixing the mixed liquid obtained in the first step with an active material to obtain a positive electrode composition.

[0020] In the second step of the first embodiment, the method of mixing the mixed liquid and the active material is not particularly limited, and may be performed by a known method (e.g., stirring and mixing using a ball mill, a sand mill, a two-axis kneader, a rotation-revolution type stirrer, a planetary mixer, a dispersing mixer, etc.). The second step of the first embodiment may be, for example, a step of adding an active material to a mixing vessel containing the mixed liquid, and then stirring to obtain a positive electrode composition.

[0021] In a second aspect, a method for producing a positive electrode composition includes a first step of mixing a first agent containing a binder and a first liquid medium with a second agent containing carbon black and a second liquid medium to obtain a first mixed liquid, a second step of mixing the first mixed liquid with a third agent containing carbon nanotubes and a third liquid medium to obtain a second mixed liquid, and a third step of mixing the second mixed liquid with an active material to obtain a positive electrode composition.

[0022] According to the second aspect, a positive electrode composition capable of realizing excellent discharge rate characteristics and cycle characteristics can be obtained, compared with the case where carbon black, carbon nanotubes, a binder, and an active material are simultaneously mixed. The reason why the above-mentioned effect is achieved by the manufacturing method of the first aspect is considered to be that in the first step, a dispersion state in which the binder and carbon black are less likely to aggregate and are less likely to be entangled with the carbon nanotubes is realized due to the interaction between the binder and the carbon black, and thus the non-uniformity of the electrode structure caused by the aggregation of carbon black or the entanglement of carbon black and carbon nanotubes is suppressed.

[0023] The first step of the second embodiment is a step of mixing a first agent containing a binder and a first liquid medium with a second agent containing carbon black and a second liquid medium to obtain a first mixed liquid.

[0024] In the first step of the second embodiment, the method of mixing the first and second agents is not particularly limited, and may be carried out by a known method (e.g., stirring and mixing using a ball mill, a sand mill, a twin-screw kneader, a centrifugal mixer, a planetary mixer, a dispersing mixer, etc.). The first step of the second embodiment may be, for example, a step of adding the first and second agents to a mixing vessel and then stirring to obtain a first mixed solution.

[0025] The second step of the second embodiment is a step of mixing the first mixture obtained in the first step with a third agent containing carbon nanotubes and a third liquid medium to obtain a second mixture.

[0026] In the second step of the second embodiment, the method of mixing the first mixed liquid and the third agent is not particularly limited, and may be carried out by a known method (e.g., stirring and mixing using a ball mill, a sand mill, a twin-screw kneader, a centrifugal mixer, a planetary mixer, a dispersing mixer, etc.). The second step of the second embodiment may be, for example, a step of adding the third agent to a mixing vessel containing the first mixed liquid, and then stirring to obtain the second mixed liquid.

[0027] The third step of the second embodiment is a step of mixing the second mixture obtained in the second step with an active material to obtain a positive electrode composition.

[0028] In the third step of the second embodiment, the method of mixing the second mixed liquid and the active material is not particularly limited, and may be performed by a known method (e.g., stirring and mixing using a ball mill, a sand mill, a two-axis kneader, a centrifugal mixer, a planetary mixer, a dispersing mixer, etc.). The third step of the second embodiment may be, for example, a step of adding an active material to a mixing vessel containing the second mixed liquid, and then stirring to obtain a positive electrode composition.

[0029] Each component used in the method for producing the positive electrode composition of this embodiment will be described in detail below.

[0030] The first agent includes a binder and a first liquid medium.

[0031] Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, and (meth)acrylic acid ester copolymer. The polymer structure of the binder may be, for example, a random copolymer, an alternating copolymer, a graft copolymer, a block copolymer, etc. As the binder, polyvinylidene fluoride is preferable from the viewpoint of excellent voltage resistance.

[0032] The content of the binder in the first agent is not particularly limited, and may be appropriately changed so that the content of the binder in the positive electrode composition is within a desired range. The content of the binder in the positive electrode composition may be, for example, 0.3 mass% or more based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of further improving the binding property of the positive electrode plate and further improving the cycle characteristics, it may be 0.5 mass% or more, 1.0 mass% or more, or 1.5 mass% or more. The content of the binder in the positive electrode composition may be, for example, 5.0 mass% or less based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of further reducing the resistance of the positive electrode plate and further improving the discharge rate characteristics, it may be 4.5 mass% or less, 4.0 mass% or less, or 3.5 mass% or less. That is, the content of the binder in the positive electrode composition may be, for example, 0.3 to 5.0 mass%, 0.3 to 4.5 mass%, 0.3 to 4.0 mass%, 0.3 to 3.5 mass%, 0.5 to 5.0 mass%, 0.5 to 4.5 mass%, 0.5 to 4.0 mass%, 0.5 to 3.5 mass%, 1.0 to 5.0 mass%, 1.0 to 4.5 mass%, 1.0 to 4.0 mass%, 1.0 to 3.5 mass%, 1.5 to 5.0 mass%, 1.5 to 4.5 mass%, 1.5 to 4.0 mass%, or 1.5 to 3.5 mass%, based on the total mass of the solids in the positive electrode composition.

[0033] The first liquid medium is not particularly limited as long as it can dissolve the binder and is compatible with the second and third liquid media. Examples of the first liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone. Among these, N-methyl-2-pyrrolidone is preferred from the viewpoint of solubility.

[0034] The content of the first liquid medium in the first agent is not particularly limited as long as it is within a range in which the binder can be dissolved, and may be appropriately changed so that the solids concentration of the positive electrode composition falls within a desired range.

[0035] The solid content concentration of the first agent is not particularly limited, and may be, for example, 1.0 mass% or more, 2.0 mass% or more, 3.0 mass% or more, or 4.0 mass% or more. The solid content concentration of the first agent may be, for example, 11.0 mass% or less, 10.0 mass% or less, or 9.0 mass% or less. That is, the solid content concentration of the first agent may be, for example, 1.0 to 11.0 mass%, 1.0 to 10.0 mass%, 1.0 to 9.0 mass%, 2.0 to 11.0 mass%, 2.0 to 10.0 mass%, 2.0 to 9.0 mass%, 3.0 to 11.0 mass%, 3.0 to 10.0 mass%, 3.0 to 9.0 mass%, 4.0 to 11.0 mass%, 4.0 to 10.0 mass%, or 4.0 to 9.0 mass%.

[0036] The first agent may further contain components other than the binder and the first liquid medium, such as polyvinylpyrrolidone, polyvinylimidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethyl cellulose, acetyl cellulose, or a carboxylic acid-modified (meth)acrylic acid ester copolymer.

[0037] The second agent includes carbon black and a second liquid medium.

[0038] The carbon black may be any carbon black commonly used as a conductive material for batteries, such as acetylene black, furnace black, channel black, etc. The carbon black is preferably acetylene black, from the viewpoint of excellent purity and ease of obtaining excellent battery characteristics.

[0039] Carbon black: 100 to 400 m 2 Carbon black having a BET specific surface area of ​​100 nm / g and a crystallite size (Lc) of 15 to 26 Å is preferred.

[0040] The BET specific surface area of ​​carbon black is 100m 2 / g or more. The BET specific surface area of ​​the carbon blank is preferably 100 m 2With a specific surface area of ​​130 m / g or more, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting electrical conductivity is improved, resulting in better battery characteristics. The BET specific surface area of ​​the carbon black is preferably 130 m from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g or more, more preferably 150m 2 / g or more, 170m 2 / g or more, 200m 2 / g or more, 240m 2 / g or more, 280m 2 / g or more, 320m 2 / g or more, or 360m 2 / g or more.

[0041] The BET specific surface area of ​​carbon black is 400m 2 The BET specific surface area of ​​the carbon black is preferably 400 m 2 When the BET specific surface area of ​​the carbon black is less than 350 m / g, the interaction between the liquid medium and the conductive material and the interaction between the conductive materials are small, and the conductive material is easily dispersed uniformly in the active material. This makes it easier to form a conductive path, and better battery characteristics are obtained. From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the BET specific surface area of ​​the carbon black is preferably 350 m 2 / g or less, and more preferably 300m 2 / g or less, 250m 2 / g or less, or 150m 2 / g or less. That is, the BET specific surface area of ​​carbon black is, for example, 100 to 400 m 2 / g, 100-350m 2 / g, 100-300m 2 / g, 100-250m 2 / g, 100-150m 2 / g, 130-400m 2 / g, 130-350m 2 / g, 130-300m 2 / g, 130-250m 2 / g, 130-150m2 / g, 150-400m 2 / g, 150-350m 2 / g, 150-300m 2 / g, 150-250m 2 / g, 170-400m 2 / g, 170-350m 2 / g, 170-300m 2 / g, 170-250m 2 / g, 170-150m 2 / g, 200-400m 2 / g, 200-350m 2 / g, 200-300m 2 / g, 200-250m 2 / g, 240-400m 2 / g, 240-350m 2 / g, 240-300m 2 / g, 240-250m 2 / g, 280-400m 2 / g, 280-350m 2 / g, 280-300m 2 / g, 320-400m 2 / g, 320-350m 2 / g or 360~400m 2 / g.

[0042] The BET specific surface area of ​​carbon black can be measured by a static capacitance method in accordance with JIS Z8830 using nitrogen as an adsorbate.

[0043] The crystallite size (Lc) of the carbon black is preferably 15 Å or more. When the crystallite size (Lc) is 15 Å or more, π electrons can easily move in the crystal layer, and a conductive path that carries electrons flowing from the current collector to the active material can be more easily formed, resulting in better battery characteristics. The crystallite size (Lc) of the carbon black may be 16 Å or more, 18 Å or more, or 20 Å or more.

[0044] In addition, the crystallite size (Lc) of the carbon black is preferably 26 Å or less. With a crystallite size (Lc) of 26 Å or less, the particle shape of the carbon black is more likely to be rounded, so that the interaction between particles is reduced and the carbon black is more likely to be dispersed more uniformly in the active material, which makes it easier to form a conductive path and obtains better battery characteristics. From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the crystallite size (Lc) of the carbon black is preferably 24 Å or less, and may be 22 Å or less or 20 Å or less. That is, the crystallite size (Lc) of the carbon black may be, for example, 15 to 26 Å, 15 to 24 Å, 15 to 22 Å, 15 to 20 Å, 16 to 26 Å, 16 to 24 Å, 16 to 22 Å, 16 to 20 Å, 18 to 26 Å, 18 to 24 Å, 18 to 22 Å, 18 to 20 Å, 20 to 26 Å, 20 to 24 Å, or 20 to 22 Å.

[0045] The crystallite size (Lc) of carbon black is measured in accordance with JIS R 7651. The crystallite size (Lc) of carbon black means the crystallite size in the c-axis direction of the carbon black crystal layer.

[0046] The average primary particle size of carbon black is preferably 17 nm or more. When the average primary particle size of carbon black is 17 nm or more, the interaction between the liquid medium and the conductive material and the interaction between the conductive materials are reduced, which makes it easier to disperse the carbon black more uniformly in the active material, makes it easier to form a conductive path, and makes it easier to obtain excellent battery characteristics. The average primary particle size of carbon black may be 18 nm or more, 19 nm or more, or 20 nm or more.

[0047] In addition, the average primary particle diameter of the carbon black is preferably 30 nm or less. When the average primary particle diameter of the carbon black is 30 nm or less, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting electrical conductivity is good, so that excellent battery characteristics are more easily obtained. From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the average primary particle diameter of the carbon black is preferably 26 nm or less, and may be 24 nm or less, 22 nm or less, or 20 nm or less. That is, the average primary particle diameter of carbon black may be, for example, 17 to 30 nm, 17 to 26 nm, 17 to 24 nm, 17 to 22 nm, 17 to 20 nm, 18 to 30 nm, 18 to 26 nm, 18 to 24 nm, 18 to 22 nm, 18 to 20 nm, 19 to 30 nm, 19 to 26 nm, 19 to 24 nm, 19 to 22 nm, 19 to 20 nm, 20 to 30 nm, 20 to 26 nm, 20 to 24 nm, or 20 to 22 nm.

[0048] The average primary particle diameter of carbon black means the average circle-equivalent diameter measured based on images of carbon black observed with a transmission electron microscope (TEM). Specifically, a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.) is used to capture 10 images of carbon black at 100,000 times magnification, and the circle-equivalent diameters of 200 primary particles of carbon black randomly selected from the resulting images are measured by image analysis, and the arithmetic mean is calculated.

[0049] When the peak area of ​​the peak at mass number m / z 57 detected by thermal desorption spectrometry of carbon black is S1 and the peak area of ​​the peak at mass number m / z 128 is S2, the ratio of the peak area S2 to the peak area S1 (S2 / S1) is preferably 0.2 to 1.9. The ratio (S2 / S1) indicates the proportion of organic components adsorbed on the surface of the carbon black. When the ratio (S2 / S1) is 1.9 or less, the organic components adsorbed on the surface of the carbon black are sufficiently reduced, and the decrease in conductivity caused by the organic components trapping π electrons is significantly suppressed. In addition, when the ratio (S2 / S1) is 0.2 or more, the organic components adsorbed on the surface of the carbon black play the role of a dispersant, improving the dispersibility in the liquid medium, and thus further reducing the slurry viscosity. The peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128 can be measured by evolved gas mass spectrometry (EGA-MS). For example, carbon black is placed in a gas chromatograph mass spectrometer having a pyrolysis device, and is held at 50°C for 5 minutes in an atmospheric pressure He flow, and then heated to 800°C at 80°C / min, and mass analysis is performed on the components desorbed by the temperature increase, whereby the peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128 can be measured.

[0050] From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the ratio (S2 / S1) may be 1.5 or less, 1.0 or less, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. The ratio (S2 / S1) may be 0.25 or more, or 0.3 or more. That is, the ratio (S2 / S1) may be, for example, 0.2 to 1.9, 0.2 to 1.5, 0.2 to 1.0, 0.2 to 0.8, 0.2 to 0.6, 0.2 to 0.5, 0.2 to 0.4, 0.2 to 0.3, 0.25 to 1.9, 0.25 to 1.5, 0.25 to 1.0, 0.25 to 0.8, 0.25 to 0.6, 0.25 to 0.5, 0.25 to 0.4, 0.25 to 0.3, 0.3 to 1.9, 0.3 to 1.5, 0.3 to 1.0, 0.3 to 0.8, 0.3 to 0.6, 0.3 to 0.5, or 0.3 to 0.4.

[0051] From the viewpoint of excellent electrical conductivity, the volume resistivity of carbon black may be 0.30 Ω·cm or less or 0.25 Ω·cm or less. The volume resistivity of carbon black is measured in a compressed state under a load of, for example, 7.5 MPa.

[0052] The ash content and moisture content of the carbon black are not particularly limited. The ash content of the carbon black may be, for example, 0.04% by mass or less, and the moisture content of the carbon black may be, for example, 0.10% by mass or less.

[0053] The method for producing carbon black is not particularly limited. For example, the carbon black may be produced by a production method including a synthesis step of treating a raw material gas containing a hydrocarbon in a cylindrical cracking furnace to obtain carbon black, and a purification step of removing magnetic foreign matter from the carbon black obtained in the synthesis step by using a magnet.

[0054] In the synthesis step, the raw material gas is treated in a cylindrical cracking furnace. The cylindrical cracking furnace may, for example, include a pyrolysis section for carrying out a pyrolysis reaction of hydrocarbons and an aging section for modifying the pyrolysis reaction product. The cylindrical cracking furnace may further include a supply port for supplying the raw material gas to the pyrolysis section and a recovery port for recovering the carbon black produced from the aging section.

[0055] In the thermal decomposition section, the supplied raw material gas preferably resides at a temperature of 1900°C or higher for 30 to 150 seconds. By setting the residence time of the raw material gas to 30 seconds or more, the completion of the thermal decomposition reaction and the formation of carbon aerosol due to the development of a chain structure can be more reliably carried out. Furthermore, by setting the residence time of the raw material gas to 150 seconds or less, the aggregation of carbon aerosol is suppressed, making it easier to remove magnetic foreign matter in the purification step, and making it easier to obtain high-purity carbon black.

[0056] In the maturation section, the pyrolysis reaction product supplied from the pyrolysis section preferably resides at a temperature of 1700°C or higher for 20 to 90 seconds. When the residence time of the pyrolysis reaction product is 20 seconds or more, carbon aerosol is modified and aggregate development is promoted, making it easier to obtain higher quality carbon black. Furthermore, when the residence time of the pyrolysis reaction product is 90 seconds or less, the agglomeration of carbon aerosol is suppressed, making it easier to remove magnetic foreign matter in the purification step, and making it easier to obtain high purity carbon black.

[0057] The residence times in the pyrolysis section and the aging section can be appropriately adjusted by adjusting the linear gas velocity of the gas flowing through each section. The residence time in the aging section is preferably shorter than the residence time in the pyrolysis section. That is, the linear gas velocity in the aging section is preferably faster than the linear gas velocity in the pyrolysis section.

[0058] In this embodiment, the raw material gas preferably contains acetylene as a carbon source. The content of the carbon source (e.g., acetylene) in the raw material gas is, for example, 10% by volume or more, preferably 20% by volume or more, more preferably 30% by volume or more, and may be 100% by volume. The content of each component in the raw material gas is expressed as a volume ratio based on the volume at 100°C and 1 atm.

[0059] The raw material gas may further contain other hydrocarbons other than the carbon source (e.g., acetylene). Examples of other hydrocarbons include methane, ethane, propane, ethylene, propylene, butadiene, benzene, toluene, xylene, gasoline, kerosene, light oil, heavy oil, etc. By adding these other hydrocarbons, the reaction temperature can be changed to increase or decrease the specific surface area of ​​the carbon black. The other hydrocarbons are preferably selected from the group consisting of aromatic hydrocarbons such as benzene and toluene, and unsaturated hydrocarbons such as ethylene and propylene.

[0060] When the raw material gas contains acetylene and other hydrocarbons, the content of the other hydrocarbons is, for example, 0.1 to 99 parts by volume, preferably 0.2 to 50 parts by volume, and more preferably 0.3 to 30 parts by volume, relative to 100 parts by volume of acetylene. That is, the content of the other hydrocarbons may be, for example, 0.1 to 99 parts by volume, 0.1 to 50 parts by volume, 0.1 to 30 parts by volume, 0.2 to 99 parts by volume, 0.2 to 50 parts by volume, 0.2 to 30 parts by volume, 0.3 to 99 parts by volume, 0.3 to 50 parts by volume, or 0.3 to 30 parts by volume, relative to 100 parts by volume of acetylene.

[0061] The raw material gas may further contain water vapor gas, oxygen gas, hydrogen gas, carbon dioxide gas, etc. As these gases, it is preferable to use high purity gases with a purity of 99.9% by volume or more. By using such high purity gases, it tends to be easier to produce carbon black with less magnetic foreign matter and stable BET specific surface area and oil absorption.

[0062] The content of the water vapor gas may be, for example, 0 to 80 parts by volume, preferably 0.1 to 70 parts by volume, more preferably 1 to 60 parts by volume, and even more preferably 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the content of the water vapor gas is within the above range, the BET specific surface area of ​​the carbon black tends to be larger. That is, the content of the water vapor gas may be, for example, 0 to 80 parts by volume, 0 to 70 parts by volume, 0 to 60 parts by volume, 0 to 55 parts by volume, 0.1 to 80 parts by volume, 0.1 to 70 parts by volume, 0.1 to 60 parts by volume, 0.1 to 55 parts by volume, 1 to 80 parts by volume, 1 to 70 parts by volume, 1 to 60 parts by volume, 1 to 55 parts by volume, 3 to 80 parts by volume, 3 to 70 parts by volume, 3 to 60 parts by volume, or 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source in the raw material gas.

[0063] In the synthesis process, it is preferable to supply oxygen gas to the pyrolysis section together with the raw material gas, and it is more preferable to supply the oxygen gas to the pyrolysis section by spraying the oxygen gas from around the supply port through which the raw material gas is supplied to the pyrolysis section.

[0064] The cylindrical cracking furnace preferably has an oxygen gas nozzle near the raw material gas supply port, and more preferably has a plurality of nozzles provided at equal intervals so as to surround the supply port. The number of nozzles is preferably 3 or more, more preferably 3 to 8.

[0065] The cylindrical cracking furnace may also be equipped with a nozzle having a multiple tube structure (e.g., a double tube structure, a triple tube structure, etc.) having a raw material gas supply port and an injection port for injecting oxygen gas from the periphery thereof. In the case of a double tube structure, for example, the raw material gas may be injected from a gap on the inner tube side, and the oxygen gas may be injected from a gap on the outer tube side. In the case of a triple tube structure consisting of an inner tube, a middle tube, and an outer tube, for example, the oxygen gas may be injected from a gap formed by the outer wall of the middle tube and the inner wall of the outer tube, and the raw material gas may be injected from the remaining gap.

[0066] The amount of oxygen gas injected is not particularly limited unless the production yield of carbon black is taken into consideration. Carbon black can be produced even if more oxygen gas than necessary is injected. The amount of oxygen gas injected may be, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, or 0 to 200 parts by volume, preferably 0.1 to 190 parts by volume, more preferably 0.5 to 180 parts by volume, and even more preferably 1 to 160 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the amount of oxygen gas injected is increased, the BET specific surface area of ​​the carbon black and the above ratio (S1 / S2) tend to become larger, and when the amount of oxygen gas injected is decreased, the primary particle size of the carbon black tends to become larger. That is, the injection amount of oxygen gas is, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, 0 to 200 parts by volume, 0 to 190 parts by volume, 0 to 180 parts by volume, 0 to 160 parts by volume, 0.1 to 300 parts by volume, 0.1 to 250 parts by volume, 0.1 to 220 parts by volume, 0.1 to 200 parts by volume, 0.1 to 190 parts by volume, 0.1 ... The amount may be 0 parts by volume, 0.1 to 160 parts by volume, 0.5 to 300 parts by volume, 0.5 to 250 parts by volume, 0.5 to 220 parts by volume, 0.5 to 200 parts by volume, 0.5 to 190 parts by volume, 0.5 to 180 parts by volume, 0.5 to 160 parts by volume, 1 to 300 parts by volume, 1 to 250 parts by volume, 1 to 220 parts by volume, 1 to 200 parts by volume, 1 to 190 parts by volume, 1 to 180 parts by volume, or 1 to 160 parts by volume.

[0067] In the synthesis step, the primary particle size, BET specific surface area, and crystallite size (Lc) of the resulting carbon black can be adjusted by, for example, adjusting the addition rate of hydrocarbons other than acetylene, the amount of oxygen gas injected, etc.

[0068] The purification step is a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet. The purification step may be, for example, a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step by contacting the carbon black obtained in the synthesis step with a magnet or placing the carbon black in the vicinity of a magnet (for example, passing the carbon black in the vicinity of a magnet).

[0069] The maximum surface magnetic flux density of the magnet is not particularly limited, but may be, for example, 700 mT or more, preferably 1000 mT or more, more preferably 1200 mT or more. This allows fine magnetic foreign matter attached to the carbon black to be more strongly adsorbed, making it easier to obtain carbon black with a lower nickel content. The upper limit of the maximum surface magnetic flux density of the magnet is not particularly limited, and may be, for example, 1400 mT or less. That is, the maximum surface magnetic flux density of the magnet may be, for example, 700 to 1400 mT, 1000 to 1400 mT, or 1200 to 1400 mT.

[0070] The purification step may be a step of removing magnetic foreign matter from the carbon black so that the nickel content is 50 ppb or less (preferably 40 ppb or less, more preferably 30 ppb or less, and even more preferably 20 ppb or less). There is no particular restriction on the lower limit of the nickel content, but the nickel content in the carbon black may be, for example, 1 ppb or more, and from the viewpoint of cost and productivity, it may be 10 ppb or more, or 15 ppb or more. That is, the nickel content in the carbon black may be 1 to 50 ppb, 1 to 40 ppb, 1 to 30 ppb, 1 to 20 ppb, 10 to 50 ppb, 10 to 40 ppb, 10 to 30 ppb, 10 to 20 ppb, 15 to 50 ppb, 15 to 40 ppb, 15 to 30 ppb, or 15 to 20 ppb.

[0071] The content of carbon black in the second agent is not particularly limited, and may be appropriately changed so that the content of carbon black in the positive electrode composition is within a desired range. The content of carbon black in the positive electrode composition may be, for example, 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more, based on the total mass of the solid content in the positive electrode composition. The content of carbon black in the positive electrode composition may be, for example, 10 mass% or less, 7 mass% or less, 5 mass% or less, 4 mass% or less, 3 mass% or less, or 2 mass% or less, based on the total mass of the solid content in the positive electrode composition. That is, the content of carbon black in the positive electrode composition is, for example, 0.01 to 10 mass%, 0.01 to 7 mass%, 0.01 to 5 mass%, 0.01 to 4 mass%, 0.01 to 3 mass%, 0.01 to 2 mass%, 0.05 to 10 mass%, 0.05 to 7 mass%, 0.05 to 5 mass%, 0.05 to 4 mass%, 0.05 to 3 mass%, 0.05 to 2 mass%, 0.1 to 10 mass%, 0.1 to 7 mass%, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.1 to 3 mass%, 0.1 to 2 mass%, 0.2~10 mass%, 0.2~7 mass%, 0.2~5 mass%, 0.2~4 mass%, 0.2~3 mass%, 0.2~2 mass%, 0.3~10 mass%, 0.3~7 mass%, 0.3~5 mass%, 0.3~4 mass%, 0.3~3 mass%, 0.3~2 mass%, 0.4~ It may be 10% by mass, 0.4-7% by mass, 0.4-5% by mass, 0.4-4% by mass, 0.4-3% by mass, 0.4-2% by mass, 0.5-10% by mass, 0.5-7% by mass, 0.5-5% by mass, 0.5-4% by mass, 0.5-3% by mass or 0.5-2% by mass.

[0072] The content of carbon black in the second agent may be appropriately changed so that the ratio (C1 / C2) (mass ratio) of the content of carbon black (C1) to the content of carbon nanotubes (C2) in the positive electrode composition is within a desired range. The ratio (C1 / C2) may be, for example, 0.1 or more, and from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, it may be 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more. The ratio (C1 / C2) may be, for example, 0.95 or less, and from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, it may be 0.9 or less, 0.85 or less, or 0.8 or less. That is, the ratio (C1 / C2) may be, for example, 0.1 to 0.95, 0.1 to 0.9, 0.1 to 0.85, 0.1 to 0.8, 0.3 to 0.95, 0.3 to 0.9, 0.3 to 0.85, 0.3 to 0.8, 0.4 to 0.95, 0.4 to 0.9, 0.4 to 0.85, 0.4 to 0.8, 0.5 to 0.95, 0.5 to 0.9, 0.5 to 0.85, 0.5 to 0.8, 0.6 to 0.95, 0.6 to 0.9, 0.6 to 0.85, or 0.6 to 0.8.

[0073] The second liquid medium is not particularly limited as long as it can disperse carbon black and has compatibility with the first and third liquid media. Examples of the second liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone. Among these, N-methyl-2-pyrrolidone is preferred from the viewpoint of easy dispersion of carbon black. The second liquid medium may be the same as or different from the first and third liquid media, but is preferably the same as the first and third liquid media.

[0074] The content of the second liquid medium in the second agent is not particularly limited as long as it is within a range in which carbon black can be dispersed, and may be appropriately changed so that the solids concentration of the positive electrode composition falls within a desired range.

[0075] The solid content concentration of the second agent is not particularly limited and may be, for example, 1.5% by mass or more, 2.5% by mass or more, 3.5% by mass or more, or 5.0% by mass or more. The solid content concentration of the second agent may be, for example, 25.0% by mass or less, 22.0% by mass or less, 20.0% by mass or less, or 18.0% by mass or less. That is, the solids concentration of the second agent may be, for example, 1.5 to 25.0 mass%, 1.5 to 22.0 mass%, 1.5 to 20.0 mass%, 1.5 to 18.0 mass%, 2.5 to 25.0 mass%, 2.5 to 22.0 mass%, 2.5 to 20.0 mass%, 2.5 to 18.0 mass%, 3.5 to 25.0 mass%, 3.5 to 22.0 mass%, 3.5 to 20.0 mass%, 3.5 to 18.0 mass%, 5.0 to 25.0 mass%, 5.0 to 22.0 mass%, 5.0 to 20.0 mass%, or 5.0 to 18.0 mass%.

[0076] The second agent may further contain components other than the carbon black and the second liquid medium, such as polyvinylpyrrolidone, polyvinylimidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethyl cellulose, acetyl cellulose, or a carboxylic acid-modified (meth)acrylic acid ester copolymer.

[0077] The third agent includes carbon nanotubes and a third liquid medium.

[0078] The carbon nanotubes have an average diameter of 5 to 15 nm, and the ratio of the average diameter to the BET specific surface area (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 Carbon nanotubes having a small average diameter of 5 to 15 nm and a ratio of the average diameter to the BET specific surface area of ​​0.01 to 0.068 nm / (m 2 / g), more conductive paths can be formed in the positive electrode.

[0079] The average diameter of the carbon nanotubes is preferably 5 nm or more. When the average diameter of the carbon nanotubes is 5 nm or more, the interaction between the liquid medium and the conductive material and the interaction between the conductive materials are reduced, and the carbon nanotubes are more easily dispersed uniformly in the active material. This makes it easier to form a conductive path, and better battery characteristics are obtained. The average diameter of the carbon nanotubes may be 6 nm or more.

[0080] In addition, the average diameter of the carbon nanotubes is preferably 15 nm or less. By having the average diameter of the carbon nanotubes be 15 nm or less, the number of electrical contacts between the active material and the conductive material increases, the effect of imparting electrical conductivity is improved, and better battery characteristics are easily obtained. From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the average diameter of the carbon nanotubes is preferably 12 nm or less, more preferably 10 nm or less, and may be 9 nm or less, 8 nm or less, or 7 nm or less. That is, the average diameter of the carbon nanotubes may be, for example, 5 to 15 nm, 5 to 12 nm, 5 to 10 nm, 5 to 9 nm, 5 to 8 nm, 5 to 7 nm, 6 to 15 nm, 6 to 12 nm, 6 to 10 nm, 6 to 9 nm, 6 to 8 nm, or 6 to 7 nm.

[0081] The average diameter of carbon nanotubes means the average diameter measured based on images of carbon nanotubes observed with a transmission electron microscope (TEM); specifically, a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.) is used to capture 10 images of carbon nanotubes at 200,000 magnification, and the diameters of 100 carbon nanotubes randomly selected from the resulting images are measured by image analysis, and the arithmetic average is calculated.

[0082] The BET specific surface area of ​​carbon nanotubes is 170 to 320 m 2 / g. The BET specific surface area of ​​the carbon nanotubes is preferably 170 m 2When the BET specific surface area of ​​the carbon nanotubes is 320 m / g or more, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting conductivity is good, making it easier to obtain excellent battery characteristics. 2 / g or less, the interaction between the liquid medium and the conductive material, and between the conductive materials themselves, is reduced, making it easier for the conductive material to be dispersed more uniformly in the active material. This makes it easier to form conductive paths, making it easier to obtain better battery characteristics. The BET specific surface area of ​​carbon nanotubes can be measured by the static capacitance method in accordance with JIS Z8830, using nitrogen as the adsorbate.

[0083] The BET specific surface area of ​​carbon nanotubes is set to 180 m from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g or more, 200m 2 / g or more, 230m 2 / g or more, 250m 2 / g or more, 280m 2 / g or more, or 300m 2 The BET specific surface area of ​​the carbon nanotubes may be 300 m / g or more from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g or less. That is, the BET specific surface area of ​​the carbon nanotube may be, for example, 170 to 320 m 2 / g, 180-320m 2 / g, 200-320m 2 / g, 230-320m 2 / g, 250-320m 2 / g, 280-320m 2 / g, 300-320m 2 / g, 170-300m 2 / g, 180-300m 2 / g, 200-300m 2 / g, 230-300m 2 / g, 250-300m 2 / g or 280~300m 2 / g.

[0084] The ratio of the average diameter to the BET specific surface area of ​​carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 The ratio (average diameter / BET specific surface area) is the value obtained by dividing the average diameter of the carbon nanotubes by the BET specific surface area of ​​the carbon nanotubes. 2 / g) or more, the carbon nanotubes are less likely to be entangled with each other and are more likely to be dispersed uniformly in the active material. This makes it easier to form conductive paths, resulting in better battery characteristics. The ratio (average diameter / BET specific surface area) is 0.068 nm / (m 2 / g or less, the number of carbon nanotubes per unit weight increases, allowing electricity to flow more efficiently throughout the active material, resulting in better battery characteristics.

[0085] The ratio (average diameter / BET specific surface area) is set to 0.06 nm / (m from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g) or less, 0.04nm / (m 2 / g) or less, 0.03nm / (m 2 / g) or less, or 0.02 nm / (m 2 The ratio (average diameter / BET specific surface area) may be 0.02 nm / (m2 / g) or less from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g) or more. That is, the ratio (average diameter / BET specific surface area) may be, for example, 0.01 to 0.068 nm / (m 2 / g), 0.01~0.04nm / (m 2 / g), 0.01~0.03nm / (m 2 / g), 0.01~0.02nm / (m 2 / g), 0.02~0.068nm / (m 2 / g), 0.02~0.04nm / (m 2 / g) or 0.02~0.03nm / (m 2 / g).

[0086] The method for producing the carbon nanotubes is not particularly limited, and the carbon nanotubes may be produced by, for example, a conventionally known method for producing carbon nanotubes.

[0087] Carbon nanotubes can be produced, for example, by placing a powdered catalyst in which iron is supported on magnesia (magnesium oxide) over the entire horizontal cross section of a vertical reactor, flowing methane vertically through the reactor, contacting the methane with the catalyst at 500 to 1200°C, and then oxidizing the resulting product (unoxidized carbon nanotubes). By this method of producing carbon nanotubes, carbon nanotubes consisting of several graphene layers, with an average diameter of 5 to 15 nm and a BET specific surface area of ​​160 to 300 nm can be produced. 2 / g of carbon nanotubes can be easily obtained.

[0088] The oxidation treatment of the product may be, for example, a calcination treatment. The temperature of the calcination treatment is not particularly limited, and may be, for example, 300 to 1000°C. The temperature of the calcination treatment is affected by the atmospheric gas, so it is preferable to perform the calcination treatment at a relatively low temperature when the oxygen concentration is high, and at a relatively high temperature when the oxygen concentration is low. Specifically, the calcination treatment of the product may be performed in the atmosphere within a range of ±50°C of the combustion peak temperature of the carbon nanotubes before the oxidation treatment. When the oxygen concentration is higher than that of the atmosphere, the calcination is performed at a temperature range lower than the calcination peak temperature, and when the oxygen concentration is lower than that of the atmosphere, a temperature range higher than the calcination peak temperature is selected. In particular, when performing the calcination treatment of the carbon nanotubes before the oxidation treatment in the atmosphere, it is preferable to perform the calcination treatment within a range of ±15°C of the combustion peak temperature of the carbon nanotubes before the oxidation treatment.

[0089] The oxidation treatment of the above product may be a treatment with hydrogen peroxide, mixed acid, nitric acid, or the like. As a method of treating the above product with hydrogen peroxide, for example, a method of mixing the above product in 34.5% hydrogen peroxide water to 0.01 to 10 mass % and reacting at a temperature of 0 to 100 ° C. for 0.5 to 48 hours can be mentioned. In addition, as a method of treating the above product with mixed acid, for example, a method of mixing the above product in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: concentrated nitric acid = 3: 1) to 0.01 to 10 mass % and reacting at a temperature of 0 to 100 ° C. for 0.5 to 48 hours can be mentioned. The mixing ratio of the mixed acid (concentrated sulfuric acid: concentrated nitric acid) can be adjusted within the range of 1: 10 to 10: 1 according to the amount of single-walled carbon nanotubes in the above product. An example of a method for treating the above product with nitric acid is to mix the above product with nitric acid having a concentration of 40 to 80% by mass so that the concentration is 0.01 to 10% by mass, and react the mixture at a temperature of 60 to 150° C. for 0.5 to 48 hours.

[0090] By subjecting the above-mentioned product to an oxidation treatment, impurities such as amorphous carbon and single-walled carbon nanotubes having low heat resistance in the product can be selectively removed, and the purity of several graphene layers, particularly carbon nanotubes having 2 to 5 layers, can be improved. At the same time, by subjecting the product to an oxidation treatment, functional groups are added to the surface of the carbon nanotubes, improving the affinity with the dispersion medium and additives and improving the dispersibility. Among the above-mentioned oxidation treatments, a treatment using nitric acid is preferred.

[0091] The oxidation treatment may be performed immediately after obtaining carbon nanotubes before the oxidation treatment, or after another purification treatment. For example, when iron / magnesia is used as a catalyst, the oxidation treatment may be performed after a purification treatment with an acid such as hydrochloric acid to remove the catalyst before the oxidation treatment, or the oxidation treatment may be performed after the purification treatment to remove the catalyst.

[0092] The content of carbon nanotubes in the third agent is not particularly limited, and may be appropriately changed so that the content of carbon nanotubes in the positive electrode composition is within a desired range. The content of carbon nanotubes in the positive electrode composition may be, for example, 0.01% by mass or more based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, it may be 0.03% by mass or more, 0.05% by mass or more, 0.07% by mass or more, 0.1% by mass or more, or 0.2% by mass or more. In addition, the content of carbon nanotubes in the positive electrode composition may be, for example, 5% by mass or less based on the total mass of the solid content in the positive electrode composition, and may be 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.9% by mass or less, 0.8% by mass or less, or 0.7% by mass or less. That is, the content of carbon nanotubes in the positive electrode composition is, for example, 0.01 to 5 mass%, 0.01 to 3 mass%, 0.01 to 2 mass%, 0.01 to 1 mass%, 0.01 to 0.9 mass%, 0.01 to 0.8 mass%, 0.01 to 0.7 mass%, 0.03 to 5 mass%, 0.03 to 3 mass%, 0.03 to 2 mass%, 0.03 to 1 mass%, 0.03 to 0.9 mass%, 0.03 to 0.8 mass%, 0.03 to 0.7 mass%, 0.05 to 5 mass%, 0.05 to 3 mass%, 0.05 to 2 mass%, 0.05 to 1 mass%, 0.05 to 0 mass%, or .9 mass%, 0.05~0.8 mass%, 0.05~0.7 mass%, 0.07~5 mass%, 0.07~3 mass%, 0.07~2 mass%, 0.07~1 mass%, 0.07~0.9 mass%, 0.07~0.8 mass%, 0.07~0.7 mass%, 0.1~5 mass%, 0.1~3 mass%, 0. It may be 1-2% by mass, 0.1-1% by mass, 0.1-0.9% by mass, 0.1-0.8% by mass, 0.1-0.7% by mass, 0.2-5% by mass, 0.2-3% by mass, 0.2-2% by mass, 0.2-1% by mass, 0.2-0.9% by mass, 0.2-0.8% by mass or 0.2-0.7% by mass.

[0093] The content of carbon nanotubes in the third agent may be appropriately changed so that the ratio (C1 / C2) (mass ratio) of the content of carbon black (C1) to the content of carbon nanotubes (C2) in the positive electrode composition is within a desired range. The ratio (C1 / C2) may be, for example, 0.1 or more, and from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, it may be 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more. The ratio (C1 / C2) may be, for example, 0.95 or less, and from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, it may be 0.9 or less, 0.85 or less, or 0.8 or less. That is, the ratio (C1 / C2) may be, for example, 0.1 to 0.95, 0.1 to 0.9, 0.1 to 0.85, 0.1 to 0.8, 0.3 to 0.95, 0.3 to 0.9, 0.3 to 0.85, 0.3 to 0.8, 0.4 to 0.95, 0.4 to 0.9, 0.4 to 0.85, 0.4 to 0.8, 0.5 to 0.95, 0.5 to 0.9, 0.5 to 0.85, 0.5 to 0.8, 0.6 to 0.95, 0.6 to 0.9, 0.6 to 0.85, or 0.6 to 0.8.

[0094] The third liquid medium is not particularly limited as long as it can disperse carbon nanotubes and has compatibility with the first and second liquid media. Examples of the third liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone. Among these, N-methyl-2-pyrrolidone is preferred from the viewpoint of easy dispersion of carbon nanotubes. The third liquid medium may be the same as or different from the first and second liquid media, but is preferably the same as the first and second liquid media.

[0095] The content of the third liquid medium in the third agent is not particularly limited as long as it is within a range in which the carbon nanotubes can be dispersed, and may be appropriately changed so that the solids concentration of the positive electrode composition falls within a desired range.

[0096] The solid content concentration of the third agent is not particularly limited and may be, for example, 0.2 mass% or more, 0.8 mass% or more, 1.5 mass% or more, or 2.5 mass% or more. The solid content concentration of the third agent may be, for example, 15.0 mass% or less, 12.5 mass% or less, 10.0 mass% or less, or 7.5 mass% or less. That is, the solids concentration of the third agent may be, for example, 0.2 to 15 mass%, 0.2 to 12.5 mass%, 0.2 to 10.0 mass%, 0.2 to 7.5 mass%, 0.8 to 15 mass%, 0.8 to 12.5 mass%, 0.8 to 10.0 mass%, 0.8 to 7.5 mass%, 1.5 to 15 mass%, 1.5 to 12.5 mass%, 1.5 to 10.0 mass%, 1.5 to 7.5 mass%, 2.5 to 15 mass%, 2.5 to 12.5 mass%, 2.5 to 10.0 mass%, or 2.5 to 7.5 mass%.

[0097] The third agent may further contain components other than the carbon nanotubes and the third liquid medium, such as polyvinylpyrrolidone, polyvinylimidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethyl cellulose, acetyl cellulose, or a carboxylic acid-modified (meth)acrylic acid ester copolymer.

[0098] The active material may be any material capable of reversibly absorbing and releasing cations. 4 The lithium-containing composite oxide may be a lithium-containing polyanion compound or a lithium-containing composite oxide containing manganese with a resistivity of Ω·cm or more. Examples of the lithium-containing composite oxide containing manganese include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x Lithium manganese oxide such as LiMnO4 (where x = 0 to 0.33); x Ni y Co z O2 (however, x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1), Li 1+x Mn 2-x-y M y O4 (x=0~0.33, y=0~1.0, 2-xy>0), LiMn 2-x M xExamples of the lithium-containing polyanion compound include polyanion compounds such as LiFePO4, LiMnPO4, and Li2MPO4F (wherein M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). In each composition formula, M is at least one metal selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.

[0099] Average particle diameter of active material (D 50 ) may be 20 μm or less or 10 μm or less from the viewpoint that the binding property between the conductive material and the binder is sufficiently excellent and a battery having excellent cycle characteristics can be easily obtained. 50 ) can be measured by laser light scattering.

[0100] The amount of the active material used may be appropriately changed so that the content of the active material in the positive electrode composition is within a desired range. The content of the active material in the positive electrode composition may be, for example, 80% by mass or more based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of further improving the battery characteristics, it is preferably 85% by mass or more, and may be 87% by mass or more, 90% by mass or more, 92% by mass or more, or 95% by mass. In addition, the content of the active material in the positive electrode composition may be, for example, 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, or 98% by mass or less based on the total mass of the solid content in the positive electrode composition. That is, the content of the active material in the positive electrode composition may be, for example, 80 to 99.9 mass%, 80 to 99.5 mass%, 80 to 99 mass%, 80 to 98 mass%, 85 to 99.9 mass%, 85 to 99.5 mass%, 85 to 99 mass%, 85 to 98 mass%, 87 to 99.9 mass%, 87 to 99.5 mass%, 87 to 99 mass%, 87 to 98 mass%, 90 to 99.9 mass%, 90 to 99.5 mass%, 90 to 99 mass%, 90 to 98 mass%, 92 to 99.9 mass%, 92 to 99.5 mass%, 92 to 99 mass%, 92 to 98 mass%, 95 to 99.9 mass%, 95 to 99.5 mass%, 95 to 99 mass%, or 95 to 98 mass%, based on the total mass of the solid content in the positive electrode composition.

[0101] The positive electrode composition obtained by the manufacturing method of this embodiment contains a binder, carbon black, carbon nanotubes, and an active material. The preferred range of the content of each component in the positive electrode composition is as described above.

[0102] The solid content concentration of the positive electrode composition is not particularly limited, and may be, for example, 50% by mass or more, and from the viewpoint of increasing dispersibility and improving discharge rate characteristics and cycle characteristics, it is preferably 55% by mass or more, more preferably 60% by mass or more, and may be 65% by mass or more or 70% by mass or more. The solid content concentration of the positive electrode composition may be, for example, 90% by mass or less, and from the viewpoint of decreasing the viscosity of the positive electrode composition and improving discharge rate characteristics and cycle characteristics, it is preferably 86% by mass or less, more preferably 82% by mass or less, and may be 78% by mass or less or 74% by mass or less. That is, the solid content concentration of the positive electrode composition may be, for example, 50 to 90 mass%, 50 to 86 mass%, 50 to 82 mass%, 50 to 78 mass%, 50 to 74 mass%, 55 to 90 mass%, 55 to 86 mass%, 55 to 82 mass%, 55 to 78 mass%, 55 to 74 mass%, 60 to 90 mass%, 60 to 86 mass%, 60 to 82 mass%, 60 to 78 mass%, 60 to 74 mass%, 65 to 90 mass%, 65 to 86 mass%, 65 to 82 mass%, 65 to 78 mass%, 65 to 74 mass%, 70 to 90 mass%, 70 to 86 mass%, 70 to 82 mass%, 70 to 78 mass%, or 70 to 74 mass%.

[0103] The viscosity of the positive electrode composition at 25°C and a shear rate of 10 (1 / sec) may be, for example, 6000 mPa·s or less, preferably 5000 mPa·s or less, more preferably 4000 mPa·s or less, or may be 3000 mPa·s or less. The viscosity of the positive electrode composition at 25°C and a shear rate of 10 (1 / sec) may be, for example, 500 mPa·s or more, preferably 600 mPa·s or more, more preferably 700 mPa·s or more, or may be 800 mPa·s or more. That is, the viscosity of the positive electrode composition at 25° C. and a shear rate of 10 (1 / sec) may be, for example, 500 to 6000 mPa·s, 500 to 5000 mPa·s, 500 to 4000 mPa·s, 500 to 3000 mPa·s, 600 to 6000 mPa·s, 600 to 5000 mPa·s, 600 to 4000 mPa·s, 600 to 3000 mPa·s, 700 to 6000 mPa·s, 700 to 5000 mPa·s, 700 to 4000 mPa·s, 700 to 3000 mPa·s, 800 to 6000 mPa·s, 800 to 5000 mPa·s, 800 to 4000 mPa·s, or 800 to 3000 mPa·s.

[0104] (Manufacturing method of positive electrode) The method for producing a positive electrode of the present embodiment includes a first step of producing a positive electrode composition by the above-mentioned production method, and a second step of applying the positive electrode composition onto a current collector to form a composite layer containing carbon black, carbon nanotubes, a binder, and an active material on the current collector.

[0105] In the first step, a positive electrode composition is produced by the above-mentioned production method. The first step may be a step of producing a positive electrode composition by the production method according to the first aspect described above, or may be a step of producing a positive electrode composition by the production method according to the second aspect described above.

[0106] In the second step, the positive electrode composition is applied onto a current collector to form a composite layer on the current collector. The composite layer is a layer containing the solid content of the positive electrode composition (at least carbon black, carbon nanotubes, a binder, and an active material), and may be a layer obtained by removing at least a part of the liquid medium from the positive electrode composition.

[0107] The current collector is not particularly limited, and a known current collector can be used without any particular limitation. As the current collector, for example, a metal foil (metals such as gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, and alloys mainly composed of any one of these metals) is used. Among them, it is preferable to use aluminum for the positive electrode and copper for the negative electrode. The current collector is generally provided in the form of a foil, but is not limited thereto, and a perforated foil-shaped or mesh-shaped current collector can also be used.

[0108] The method for applying the positive electrode composition onto the current collector is not particularly limited, and may be, for example, a die coating method, a dip coating method, a roll coating method, a doctor coating method, a knife coating method, a spray coating method, a gravure coating method, a screen printing method, an electrostatic coating method, or the like.

[0109] The amount of the positive electrode composition applied is not particularly limited, and may be appropriately adjusted so that the thickness of the mixture layer falls within a desired range.

[0110] The composite layer may be formed by removing at least a part of the liquid medium from the coating film of the positive electrode composition formed on the current collector. The method for removing the liquid medium is not particularly limited, and examples of the method for removing at least a part of the liquid medium by vaporizing it through heating and / or reducing pressure include leaving it to dry, using a blower dryer, a hot air dryer, an infrared heater, and a far-infrared heater.

[0111] The method for producing a positive electrode according to the present embodiment may further include a third step of pressing the mixture layer formed in the second step and the current collector in the stacking direction. The third step allows the mixture layer and the current collector to be closely attached to each other.

[0112] The method of pressing in the third step is not particularly limited, and may be, for example, a method such as roll pressing, die pressing, or calendar pressing.

[0113] The thickness of the composite layer in the positive electrode is not particularly limited, and may be, for example, 50 μm or more, and from the viewpoint of increasing the capacity of the battery, it is preferably 55 μm or more, more preferably 60 μm or more, and may be 65 μm or more or 70 μm or more. In addition, the thickness of the composite layer in the positive electrode may be, for example, 150 μm or less, and from the viewpoint of further improving the discharge rate characteristic, it is preferably 140 μm or less, more preferably 130 μm or less, and may be 120 μm or less or 110 μm or less. That is, the thickness of the composite layer in the positive electrode may be, for example, 50 to 150 μm, 50 to 140 μm, 50 to 130 μm, 50 to 120 μm, 50 to 110 μm, 55 to 150 μm, 55 to 140 μm, 55 to 130 μm, 55 to 120 μm, 55 to 110 μm, 60 to 150 μm, 60 to 140 μm, 60 to 130 μm, 60 to 120 μm, 60 to 110 μm, 65 to 150 μm, 65 to 140 μm, 65 to 130 μm, 65 to 120 μm, 65 to 110 μm, 70 to 150 μm, 70 to 140 μm, 70 to 130 μm, 70 to 120 μm, or 70 to 110 μm.

[0114] The positive electrode in this embodiment can be suitably used as the positive electrode of a battery, in particular a secondary battery (lithium ion secondary battery).

[0115] The battery (preferably a secondary battery, more preferably a lithium ion secondary battery) in this embodiment includes a positive electrode manufactured by the above-mentioned manufacturing method. In the battery of this embodiment, the configuration other than the positive electrode may be the same as that of a known battery.

[0116] The applications of the battery in this embodiment are not particularly limited, and the battery can be used in a wide range of fields, for example, portable AV devices such as digital cameras, video cameras, portable audio players, and portable LCD televisions, portable information terminals such as notebook personal computers, smartphones, and mobile PCs, as well as portable game devices, power tools, electric bicycles, hybrid automobiles, electric automobiles, and power storage systems. EXAMPLES

[0117] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0118] <Example 1> (Carbon Black) The raw material, acetylene, was pumped at 12 Nm from a nozzle installed upstream of the carbon black reactor (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 22Nm 3 / h to produce carbon black, which was then collected in a bag filter installed downstream of the reactor. The carbon black was then passed through a dry cyclone device and an iron removal magnet before being collected in a tank. The acetylene, toluene, and oxygen were heated to 115°C before being supplied to the reactor to produce carbon black A. The carbon black A thus obtained had a BET specific surface area of ​​240 m 2 / g, the average primary particle size was 20 nm, and the crystallite size (Lc) was 16 Å.

[0119] (First Agent) As the first agent, a solution of polyvinylidene fluoride in N-methyl-2-pyrrolidone (hereinafter referred to as NMP) (manufactured by Kureha Corporation, "L#7208", solid content concentration 8.0% by weight) was prepared.

[0120] (Second Agent) Carbon black A, NMP as a dispersion medium, and polyvinyl alcohol (Poval B05, manufactured by Denka Co., Ltd., saponification degree 86.5 mol%, average polymerization degree 600) as a dispersant were prepared. 1.0 mass% polyvinyl alcohol and 10.0 mass% carbon black A were added to 89.0 mass% NMP, and the mixture was stirred for 120 minutes with a planetary mixer (Hivis Dispermix 3D-5, manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black A. The obtained slurry was put into a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia beads (diameter 0.5 mm) and subjected to a dispersion treatment. After the dispersion treatment, the zirconia beads were removed by filtration to obtain a second agent.

[0121] (Third Agent) Carbon nanotubes (CNano, "Flotube6000", average diameter 6 nm, BET specific surface area 300 m 2 / g, average diameter / BET specific surface area 0.02), NMP as a dispersion medium, and polyvinylpyrrolidone (Pitzcol K90, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as a dispersant were prepared. 1.0% by mass of polyvinylpyrrolidone and 4.0% by mass of carbon nanotubes were added to 95.0% by mass of NMP, and the mixture was stirred for 120 minutes with a planetary mixer (Hivis Dispermix 3D-5, manufactured by Primix Corporation) to prepare a slurry containing carbon nanotubes. The obtained slurry was put into a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia beads (diameter 0.5 mm) and subjected to a dispersion treatment. After the dispersion treatment, the zirconia beads were removed by filtration to obtain a third agent.

[0122] (Production of Positive Electrode Composition) Average particle diameter D of active material 50 A 10 μm lithium nickel manganese cobalt oxide (Beijing Dangsheng Co., Ltd., "ME6E") was prepared. In the first step, the first agent, the second agent, and the third agent were weighed into a plastic container so that the carbon black was 0.7 parts by mass, the carbon nanotubes were 0.3 parts by mass, and the binder was 2 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a mixed solution. In the second step, 97 parts by mass of an active material was added to the mixed solution obtained in the first step, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition.

[0123] (Production of positive electrodes) The positive electrode composition was applied to one side of a 15 μm thick aluminum foil (manufactured by UACJ) by an applicator to prepare a laminate, which was then placed in a dryer and pre-dried at 105 ° C for 1 hour to completely remove the NMP. The dried laminate was then pressed with a roll press at a linear pressure of 200 kg / cm to adjust the thickness of the entire laminate to 80 μm. The laminate was then vacuum dried at 170 ° C for 3 hours to completely remove residual moisture, and a positive electrode having a current collector and a composite layer was obtained.

[0124] (Production of negative electrodes) Pure water (Kanto Chemical Co., Ltd.) was prepared as a solvent, artificial graphite (Hitachi Chemical Co., Ltd., "MAG-D") as a negative electrode active material, styrene butadiene rubber (Zeon Corporation, "BM-400B", hereinafter referred to as SBR) as a binder, and carboxymethyl cellulose (Daicel Corporation, "D2200", hereinafter referred to as CMC) as a dispersant. Next, CMC was weighed and mixed so that the solid content was 1 mass% and artificial graphite was 97 mass% in solid content, and pure water was added to this mixture, and the mixture was mixed until it was uniform using a rotation-revolution type mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a mixture. Next, SBR was weighed so that the solid content was 2 mass%, and added to the obtained mixture, and the mixture was mixed until it was uniform using a rotation-revolution type mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a negative electrode composition. Next, the negative electrode composition was applied to a copper foil (manufactured by UACJ) having a thickness of 10 μm by an applicator to prepare a laminate, which was then placed in a dryer and pre-dried at 60° C. for 1 hour. Next, the laminate was pressed with a linear pressure of 50 kg / cm using a roll press machine to adjust the thickness of the entire laminate to 60 μm. Next, the laminate was vacuum-dried at 120° C. for 3 hours to completely remove residual moisture, and a negative electrode having a current collector and a composite layer was obtained.

[0125] (Battery manufacturing) In a dry room controlled to a dew point of -50°C or less, the prepared positive electrode was processed to 40 x 40 mm, and the prepared negative electrode was processed to 44 x 44 mm, and then an aluminum tab was welded to the positive electrode and a nickel tab was welded to the negative electrode. The composite coated surfaces of the positive electrode and negative electrode were arranged to face each other in the center, and a polyolefin microporous membrane processed to 45 x 45 mm was placed between the positive electrode and negative electrode. Next, a sheet-like exterior cut and processed to a 70 x 140 mm square was folded in half at the center of the long side. Next, the exterior was arranged so that the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed to the outside of the exterior, and the laminate of the positive electrode / polyolefin microporous membrane / negative electrode was sandwiched between the folded exterior. Next, using a heat sealer, two sides of the exterior, including the side where the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed, were heat-sealed, and then 2 g of electrolyte (manufactured by Kishida Chemical, a solution containing ethylene carbonate / diethyl carbonate = 1 / 2 (volume ratio) and 1 M LiPF6 solution) was poured into the other side that was not heat-sealed, allowing the electrolyte to fully soak into the positive electrode, negative electrode, and polyolefin microporous membrane. After that, the remaining side of the exterior was heat-sealed while reducing the internal pressure using a vacuum heat sealer, to obtain a lithium-ion secondary battery.

[0126] <Example 2> The same first agent, second agent, third agent and active material as in Example 1 were prepared. In the first step, the first and second agents were weighed into a plastic container so that the carbon black was 0.7 parts by mass and the binder was 2 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a first mixture. In the second step, the third agent was added to the first mixture so that the carbon nanotubes were 0.3 parts by mass, and the mixture was mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a second mixture. In the third step, 97 parts by mass of the active material was added to the second mixed solution, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0127] <Example 3> Carbon black A with a BET specific surface area of ​​133 m 2 A second agent was prepared in the same manner as in Example 1, except that the carbon black was changed to one having a molecular weight of 1.0 / g, an average primary particle diameter of 26 nm, and a crystallite size (Lc) of 25 Å. In addition, a first agent, a third agent, and an active material similar to those in Example 1 were prepared. In the first step, the first agent, the second agent, and the third agent were weighed into a plastic container so that the carbon black was 1.4 parts by mass, the carbon nanotubes were 0.6 parts by mass, and the binder was 2 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a mixed solution. In the second step, 96 parts by mass of an active material was added to the mixed solution obtained in the first step, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0128] <Example 4> Carbon nanotubes with an average diameter of 9 nm and a BET specific surface area of ​​250 m 2 A third agent was prepared in the same manner as in Example 1, except that the carbon nanotubes used were changed to carbon nanotubes having a mean diameter / BET specific surface area of ​​0.036 (manufactured by CNano, "Flotube7000"). A positive electrode composition, a positive electrode, and a battery were produced in the same manner as in Example 1, except that this third agent was used.

[0129] <Example 5> Carbon nanotubes with an average diameter of 9 nm and a BET specific surface area of ​​250 m 2A third agent was prepared in the same manner as in Example 1, except that the carbon nanotube having a diameter / g and an average diameter / BET specific surface area of ​​0.036 (manufactured by CNano, "Flotube7000") was used. In addition, the same first agent, second agent, and active material as in Example 1 were prepared. In the first step, the first and second agents were weighed into a plastic container so that the carbon black was 0.7 parts by mass and the binder was 2 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a first mixture. In the second step, the third agent was added to the first mixture so that the carbon nanotubes were 0.3 parts by mass, and the mixture was mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a second mixture. In the third step, 97 parts by mass of the active material was added to the second mixed solution, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0130] <Comparative Example 1> The same first agent, second agent, third agent and active material as in Example 1 were prepared. The first agent, the second agent, the third agent, and the active material were weighed into a plastic container so that the carbon black was 0.7 parts by mass, the carbon nanotubes were 0.3 parts by mass, the binder was 2 parts by mass, and the active material was 97 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0131] <Comparative Example 2> The same first agent, second agent, third agent and active material as in Example 1 were prepared. In the first step, the first and third agents were weighed into a plastic container so that the carbon nanotubes were 0.3 parts by mass and the binder was 2 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a first mixture. In the second step, the second agent and the active material were added to the mixed solution obtained in the first step so that the carbon black was 0.7 parts by mass and the active material was 97 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0132] <Comparative Example 3> The same first agent, second agent, third agent and active material as in Example 1 were prepared. In the first step, the second and third agents were weighed into a plastic container so that the carbon black was 0.7 parts by mass and the carbon nanotubes were 0.3 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a mixed solution. In the second step, the first agent and the active material were added to the mixed solution obtained in the first step so that the binder was 2 parts by mass and the active material was 97 parts by mass, and mixed for 5 minutes at a revolution speed of 2000 rpm using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition. A positive electrode and a battery were produced in the same manner as in Example 1 using the obtained positive electrode composition.

[0133] The battery performance of the produced lithium ion secondary batteries was evaluated by the following method.

[0134] (Battery evaluation) [Internal resistance] The fabricated battery was charged at 25°C at 4.3V with a constant current and constant voltage of 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Next, after 5 cycles of charge / discharge under the same conditions, it was charged to a charge depth of 50%. Then, impedance measurement was performed at a frequency range of 10MHz to 0.001Hz and an oscillation voltage of 5mV to measure the internal resistance. The measurement results of the internal resistance are shown in Table 1.

[0135] [Discharge rate characteristics (rate capacity retention)] The battery thus prepared was charged at 25°C at a constant current and constant voltage of 4.3V and 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Next, the battery was again recovered and charged at a constant current and constant voltage of 4.3V and 0.2C, and then discharged to 3.0V at a constant current of 0.2C, and the discharge capacity at this time was measured. Next, the recovery charge was performed under the condition of a constant current and constant voltage of 4.3V and 0.2C, while the discharge current was changed stepwise to 0.5C, 1C, 2C, and 3C, and recovery charge and discharge were repeated to measure the discharge capacity for each discharge current. As an index of the discharge rate characteristics of the battery, the capacity retention rate at 3C discharge relative to 0.2C discharge was calculated as the rate capacity retention rate. The calculation results of the rate capacity retention rate are shown in Table 1.

[0136] [Cycle characteristics (cycle capacity retention rate)] The battery thus fabricated was charged at 25°C at a constant current and constant voltage of 4.3 V and limited to 1 C, and then discharged to 3.0 V at a constant current of 1 C. The above charge and discharge cycles were repeated 500 times, and the discharge capacity at each cycle was measured. As an index of the cycle characteristics of the battery, the capacity retention rate after 500 cycles relative to the capacity retention rate after 1 cycle was calculated as the cycle capacity retention rate. The calculation results of the cycle capacity retention rate are shown in Table 1.

[0137] [Table 1]

Claims

1. a first step of mixing a first agent containing a binder and a first liquid medium with a second agent containing carbon black and a second liquid medium to obtain a first mixed liquid; a second step of mixing the first mixture with a third agent containing carbon nanotubes and a third liquid medium to obtain a second mixture; a third step of mixing the second mixture with an active material to obtain a positive electrode composition; A method for producing a positive electrode composition comprising the steps of:

2. The carbon black has a viscosity of 100 to 400 m 2 The method according to claim 1, wherein the crystalline silica has a BET specific surface area of ​​100 nm / g and a crystallite size (Lc) of 15 to 26 Å.

3. the carbon nanotubes have an average diameter of 5 to 15 nm; The ratio of the average diameter to the BET specific surface area of ​​the carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 The method according to claim 1 or 2, wherein the molecular weight is 1 / g.

4. 3. The method according to claim 1, wherein the content of the carbon black is 40 to 90 mass % based on the total amount of the carbon black and the carbon nanotubes.

5. A first step of producing a positive electrode composition by the production method according to claim 1 or 2; a second step of applying the positive electrode composition onto a current collector to form a composite layer containing the carbon black, the carbon nanotubes, the binder, and the active material on the current collector; A method for producing a positive electrode comprising the steps of:

Citation Information

Patent Citations

  • Manufacture of electrode for non-aqueous electrolytic battery and non-aqueous electrolytic battery employing this electrode

    JP1998144302A

  • Conductive slurry, electrode slurry and electrode for electric double-layer capacitor using the slurry

    JP2008227481A

  • Positive electrode for lithium secondary battery and lithium secondary battery using the same

    JP2012038724A

  • Carbon nanotube dispersion liquid and its use

    JP2020011873A

  • Conductive material dispersion and utilization thereof

    JP2020187991A